ANATOMO-EXPERIMENTAL SUBSTANTIATION AND CLINICAL APPLICATION OF NEW MICROSURGICAL ANTIREFLUXIS ANASTOMOSES IN THE RECONSTRUCTIVE SURGERY OF EXTRAHEPATIC BILIOUS WAYS - I. I. Kagan; A. A. Tretyakov; D. Yu. Konovalov; O. B. Dronova; I. R. Kuznetsov (Креативная хирургия и онкология, 2017)
On a section material and in experiment on 195 not purebred dogs and 130 organocomplexis corpses of people working out and an anatomo-experimental substantiation of 8 new functionally active microsurgical biliodigestivе anastomoses, possessing sphincterniс and antireflux is carried out by properties. Use of principles microsurgery technique of operating solves problems of the reconstructive operations connected with application of the traditional surgical technique, such, as an inconsistency of seams biliodigestive ways, a peritonitis, relapse cicatricial stricturi, regurgitation cholangitis. In clinical practice the microsurgical technique and developed ways of biliodigestive anastomoses are applied at 67 patients with good result.